A new political economy of teacher development: England's Teaching and Leadership Innovation Fund. Issue 5 (3rd September 2021) - Ellis, Viv; Mansell, Warwick; Steadman, Sarah
ABSTRACT: This article identifies new arrangements between the state and non-state actors in the public sector, one that extends current understandings of education privatisation, the transformation of public services 'by substitution' and, specifically theories of the 'shadow state'. Drawing on data from the Political Economy of Teacher Education (PETE) project, the paper's context is the current situation of post-qualification teacher development in England and its point of departure the Teaching and Leadership Innovation Fund (TLIF) initiative, in the wider context of Conservative political interests in promoting 'social mobility' through enhancing 'teacher quality'. Through a political economy analysis of public records, course information, Freedom of Information (FOI) requests and interviews, the paper offers an emerging typology of enterprises to describe the organisations that won TLIF funding to provide Continuing Professional Development (CPD) for teachers in designated 'Opportunity Areas'. Further, the paper extends available theorisations of the shadow state by identifying three kinds of shadow state structure – autonomous, intermediate and co-created – in relation to CPD provision under TLIF. This provisional identification is offered for critical examination beyond the immediate context of English CPD policy. The paper argues that these different relations of power and interdependence represent a new political economy of teacher development in England.